Sclerotic Bone Metastasis in Pulmonary Adenocarcinoma - Riyadh Ali Mohammed Hammamy; Khalid Farooqui; Wisam Ghadban (Case Reports in Medicine)
Pulmonary adenocarcinoma is one of the major types of lung cancers in which metastasis is very common and it accounts approximately to one-third of all primary pulmonary cancers. Although a minority of patients with lung cancer are asymptomatic, which gets usually detected in routine chest radiography, most of the patients present with some symptoms. Lung cancer metastasis may occur virtually in every organ system. Patients with non-small-cell lung cancer commonly have extrathoracic metastases to the adrenal glands, liver, brain, bones, and lymph nodes at presentation. Approximately one-third of patients with lung cancer will present with symptoms related to extrathoracic spread. Metastasis to the bone is not uncommon in lung cancer; however, osteoblastic bone metastasis is very rare. Here we present a 30-year-old female diagnosed to have pulmonary adenocarcinoma with multiple sclerotic bony lesions in the vertebra.